IMPLEMENTASI MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA KELAS XI MATA PELAJARAN PKN DI SMK NURUL KAROMAH PATERONGAN GALIS BANGKALAN - Meitha Fazieska; Dian Eka Indriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning Pancasila and Citizenship Education (PPKn) in Vocational High Schools (SMK) has an important role in shaping the character and national identity of students. However, at SMK Nurul Karomah Bangkalan, the PPKn learning process still faces various obstacles, such as low student participation, lack of motivation to learn, and the dominance of lecture methods that make the classroom atmosphere passive. To overcome these problems, a more interactive and student-centered learning strategy is needed. This study aims to analyze the effectiveness of the application of the Think Pair Share (TPS) learning model in improving student learning outcomes in PPKn subjects. The subject of the study was a grade XI student of SMK Nurul Karomah. The data obtained were analyzed through the stages of reduction, presentation, and conclusion drawn, and tested for validity through triangulation and member check. The results of the study show that the application of the TPS model has a significant positive impact on improving student learning outcomes, both in the cognitive domains (increasing material understanding), affective (positive attitude towards learning), and psychomotor (communication and collaboration skills). In addition, TPS is also able to increase students' motivation and activeness in the learning process. Thus, the TPS model can be used as an alternative effective learning strategy to be applied in PPKn subjects at vocational schools.